SHAPING A HEALTHY LIFESTYLE IN STUDENTS ON THE BASIS OF MODERN PEDAGOGICAL TECHNOLOGY - Akbarova D. R. (Web of Journals Publishing, 2024)
The article talks about the skills of forming a healthy lifestyle in students based on modern pedagogical technology.
Keywords: pedagogical technology, healthy lifestyle, formation, physical education, sport, medicine, society.